Headache in General Practice: Frequency, Management, and Results of Encounter. (28th October 2014) - Frese, Thomas; Druckrey, Henriette; Sandholzer, Hagen
Abstract : Objective . Headache is a common reason for consulting the general practitioner. The goal of the investigation was to characterize the headache consultation rates, the associated symptoms, the frequency of diagnostic and therapeutic procedures, and the results of the encounter of patients with headache. Methods . Cross-sectional data were collected from randomly selected patients during the German SESAM 2 study and compared with unpublished but publicly available data from the Dutch Transition Project. Results . Headache accounts for up to five percent of all general practice consultations. Women consult the general practitioner for headache twice as often as men. Physical examination and drug prescription are the most frequent procedures. Most of the patients suffer from primary headache; secondary headache is due to upper respiratory tract infections or problems of the spinal column. Dangerous courses occur in very rare cases. Conclusion . This work confirms the findings of earlier studies regarding the management of patients that consult the general practitioner for headache. It broadens the preexisting database since cross-sectional data regarding headache in general practice was rarely published.